From Dialogism to the Theory of Intertextuality (the path of modern European culture) - Zakaryan, Hripsime (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The theory of dialogism by M. M. Bakhtin, starting from the late 1960s, after the translation and publication of his works, had a significant influence on the main directions of Western literary criticism, their theory and methodological development. Despite modern theoretical justifications for the use of the term “intertextuality,” the phenomenon of intertextuality-the idea of the interconnection of different texts-is still a long-established and well-founded reality. However, the term “intertextuality” was first coined in 1967. The term was first introduced by the poststructuralist theorist Kristeva in the article “Bakhtin, the word, dialogue and the novel”. Based on M. Bakhtin’s theory of dialogism, in her research she transforms and develops the idea of intertextual connections. Considering the theory of “polyphonism” by M. Bakhtin in the context of modern reality, Yu. Kristeva suggests that each text is in dialogue with another text or texts, each of which is capable of becoming the source material for new texts. Although the theory of intertextuality proposed by Y. Kristeva obviously receives rich charges from M. Bakhtin’s theory of dialogism, nevertheless, intertextuality is not a “mirror reflection” of the theory of dialogism, but its reinterpretation and transformation in the context of a poststructuralist concept. The article presents a comparative typological examination of M. Bakhtin’s theory of dialogism and J. Kristeva’s theory of intertextuality. Bakhtin’s concept is compared with the theory of intertextuality in Western literary criticism of a poststructuralist orientation.